IDENTIFIKASI KEBERADAAN BAKTERI COLIFORM DAN TOTAL MIKROBA DALAM ES DUNG-DUNG DI SEKITAR KAMPUS UNIVERSITAS MUHAMMADIYAH SURAKARTA[Identification of Coliform Bacteria and The Total Mikrobes in Dung-Dung Ice around Universitas Muhammadiyah Surakarta Campus] - Aprilia Mustikaning Putri; Pramudya Kurnia (Media Gizi Indonesia, 2018)
Coliform bacteria is microorganisms that can be used as indicator todefine the quality of water. Bacteria in food or drink indicates that the food may be contaminated by stool. The purpose of this research was to describe the total number of microbes and the number of bacteria coliform on “dung-dung” ice around Universitas Muhammadiyah Surakarta campus. This descriptive research used 7 samples which were taken from 7 “dung-dung” ice sellers around Muhammadiyah University of Surakarta. The samples were analyzed by using Total Plate Count (TPC) and Most Probable Number (MPN) methods. The results were compared with standard value of TPC and MPN according to the Indonesia Food and Drug Administration Regulation number 16/2016 about the criteria for food microbiology. The results of the study showed that all of the 7 samples being tested were above the standards, because the microbes count were above 105 CFU/ml (the standard is maximum 104 CFU/ml), and the MPN value > 2400 MPN/ ml (the standard is 10 APM/100ml) This study concluded that all of the “dung-dung” ice studied were  not comply the food safety standard.